Optimizing Pollution Mitigation in Textile and Leather Effluents: Evaluating Euphorbia cotinifolia and Rosa indica as Floating Wetland Species - Khan, Aisha; Butt, Saba; Anjum, Tehmina; Bilal, Zill-e-Huma; Saeed, Asma (Indus Journal of Bioscience Research, 2025)
Background: Rapid industrialization in Pakistan, particularly in the textile and leather sectors, has resulted in substantial environmental degradation due to the unchecked discharge of untreated wastewater into freshwater bodies. This study aimed to assess the phytoremediation potential of indigenous plant species for the removal of heavy metals—lead (Pb), cadmium (Cd), and copper (Cu)—from industrial effluents using floating wetlands in the Hudiara Drain, Lahore. Methods: This prospective experimental study was conducted from January 2023 to January 2024. Indigenous plant species including Iris sp., Epipremnum aureum (money plant), and Nasturtium officinale (watercress) were screened alongside Euphorbia cotinifolia (red spurge) and Rosa indica (rose) for heavy metal uptake. Parameters such as chlorophyll content, fresh and dry biomass, and metal accumulation in aerial parts were analyzed through standard spectrophotometric techniques. Morphological tolerance and metal accumulation patterns were documented. Results: Among all tested species, E. cotinifolia and R. indica exhibited superior heavy metal accumulation, especially for Pb, showing high uptake in their aerial tissues. These species also showed resilience under metal stress, maintaining chlorophyll content and biomass, indicating high tolerance. Spectroscopic analysis confirmed elevated Pb, Cd, and Cu concentrations in treated effluents. Implementation of these species in simulated floating wetland units resulted in significant metal reduction in wastewater, with Pb reduction rates exceeding 70%. Conclusion: E. cotinifolia and R. indica demonstrated strong phytoremediation potential, making them suitable candidates for use in floating wetlands for pollution control in leather and textile industry effluents. These findings support their integration into sustainable wastewater treatment strategies for SMEs in Pakistan, particularly in urban industrial zones. Adoption of such nature-based solutions could significantly mitigate the environmental burden and improve the ecological health of contaminated waterways.